2010
DOI: 10.1016/j.nbd.2010.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Cell-autonomous alteration of dopaminergic transmission by wild type and mutant (ΔE) TorsinA in transgenic mice

Abstract: Early onset torsion dystonia is an autosomal dominant movement disorder of variable caused by a glutamic acid, i.e. ΔE, deletion in DYT1, encoding the protein torsinA. Genetic and structural data implicate basal ganglia dysfunction in dystonia. TorsinA, however, is diffusely expressed, and therefore the primary source of dysfunction may be obscured in pan-neuronal transgenic mouse models. We utilized the tyrosine hydroxylase (TH) promoter to direct transgene expression specifically to dopaminergic neurons of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 52 publications
2
71
1
Order By: Relevance
“…Bao and colleagues (2010) found that transgenic DYT1 mice were more sensitive to phasic stimulation of dopamine release, an effect which was blocked by antagonism of nicotinic receptors with mecamylamine. Furthermore, mice expressing mutation of the β2 nicotinic receptor subunit do show increased sensitivity to nicotine-induced dystonic arousal complex (O'Neill et al, 2013).…”
Section: Striatal Acetylcholine Signalingmentioning
confidence: 99%
See 2 more Smart Citations
“…Bao and colleagues (2010) found that transgenic DYT1 mice were more sensitive to phasic stimulation of dopamine release, an effect which was blocked by antagonism of nicotinic receptors with mecamylamine. Furthermore, mice expressing mutation of the β2 nicotinic receptor subunit do show increased sensitivity to nicotine-induced dystonic arousal complex (O'Neill et al, 2013).…”
Section: Striatal Acetylcholine Signalingmentioning
confidence: 99%
“…Indeed loss of the dopaminergic input in Parkinson's disease models causes profound alterations in corticostriatal synaptic plasticity (Calabresi et al, 2007b), which are associated with pruning of dendritic spines on MSNs (Ingham et al, 1989; Stephens et al, 2005; Zaja-Milatovic et al, 2005; Smith and Villalba, 2008; Villalba et al, 2009; Villalba and Smith, 2010). Likewise, reduced dopamine release and changes in corticostriatal synaptic plasticity have been indicated in multiple genetic mouse models of DYT1 dystonia (Pisani et al, 2006; Balcioglu et al, 2007; Hewett et al, 2010; Page et al, 2010; Sciamanna et al, 2012; Song et al, 2012). While decreased D1 receptor activation has been linked to changes in GNAL (Corvol et al, 2007), the primary gene involved in DYT25, these mouse models have not yet been investigated for alterations in striatal synaptic plasticity.…”
Section: Striatal Circuitrymentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has not been possible to connect the molecular and cellular consequences of torsinA dysfunction to dystonic movements, as mouse models based on the manipulation of Tor1a (or other primary dystonia-causing genes) do not exhibit overt, abnormal movements. Overexpression of DYT1 mutant torsinA in mice causes modest abnormalities in measures of beam walking, pawprint analysis, and motor learning, but not abnormal movements similar to those in patients with DYT1 dystonia (22)(23)(24). DYT1 torsinA transgenic rats reportedly show hind limb clasping during tail suspension and abnormalities in the pawprint analysis (25).…”
Section: Introductionmentioning
confidence: 97%
“…Second, they may represent a novel endophenotype, i.e., a non-motor sign in mutation carriers who do not show overt motor symptoms [22,30]. The reported endophenotypes include changes in both structure [39,44] and function of the CNS [8,15,18,19,26,34,36,39]. Further elucidating the processes involved in glutamate-mediated changes in [Ca 2+ ] c dynamics is expected to help understand the pathophysiology of E-torsinA mutation.…”
Section: Discussionmentioning
confidence: 99%